Solve for f -16+5f=-7(-6+8f)+3

Math
-16+5f=-7(-6+8f)+3
Simplify -7(-6+8f)+3.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
-16+5f=-7⋅-6-7(8f)+3
Multiply -7 by -6.
-16+5f=42-7(8f)+3
Multiply 8 by -7.
-16+5f=42-56f+3
-16+5f=42-56f+3
Add 42 and 3.
-16+5f=-56f+45
-16+5f=-56f+45
Move all terms containing f to the left side of the equation.
Tap for more steps…
Add 56f to both sides of the equation.
-16+5f+56f=45
Add 5f and 56f.
-16+61f=45
-16+61f=45
Move all terms not containing f to the right side of the equation.
Tap for more steps…
Add 16 to both sides of the equation.
61f=45+16
Add 45 and 16.
61f=61
61f=61
Divide each term by 61 and simplify.
Tap for more steps…
Divide each term in 61f=61 by 61.
61f61=6161
Cancel the common factor of 61.
Tap for more steps…
Cancel the common factor.
61f61=6161
Divide f by 1.
f=6161
f=6161
Divide 61 by 61.
f=1
f=1
Solve for f -16+5f=-7(-6+8f)+3

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top